Women Entrepreneurs in Asia: Eight Country Studies. Issue 2 (May 2020) - Cho, Yonjoo; Li, Jessica; Chaudhuri, Sanghamitra
The Problem: Asia as a research context is significantly different, in many ways, from Western contexts where a majority of studies on women in leadership have been conducted. First, traditional culture and religious beliefs in Asia dictate the inferior status of women in their daily lives. Second, women's appointment to high-ranking leadership roles in Asia has been a continuing challenge. Third, many organizations in Asia remain as gendered workplaces where cultural, religious, and organizational constraints coexist. This special issue on women entrepreneurs in Asia, therefore, makes specific contributions to research on Asian women in leadership in the context of entrepreneurship. The Solution: The purpose of this special issue is to investigate women entrepreneurs' motivations, challenges, and opportunities in eight Asian countries (China, India, Indonesia, Japan, Korea, Malaysia, Thailand, and Vietnam). The special issue provides insights into developing the potential of aspiring women entrepreneurs who are set in rapidly developing Asian countries where traditional cultural and religious expectations and modernized values coexist. Despite challenges and difficulties that women entrepreneurs face, the opportunities that they create in business development can serve as a model for aspiring women entrepreneurs in Asia and other countries. The Stakeholders: As women entrepreneurs' challenges are of global interest, this special issue represents an effort to transcend national boundaries in understanding how to address the challenges they face. Scholars and practitioners who are interested in international Human Resource Development can better understand how Asia's fast-growing economies and culture have influenced women entrepreneurs in positive and negative ways.